2020
DOI: 10.1002/14651858.cd013125.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic prophylaxis to prevent spontaneous bacterial peritonitis in people with liver cirrhosis: a network meta-analysis

Abstract: Antibiotic prophylaxis to prevent spontaneous bacterial peritonitis in people with liver cirrhosis: a network meta-analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 118 publications
1
40
0
Order By: Relevance
“…However, strict study inclusion criteria with limitation to high-quality RCTs with reported follow-up intervals and the current definition of SBP resulted in a patient collective with low heterogeneity of IRRs and allowed comparison over time with regard to IRRs of SBP and extraperitoneal infections. A recent Cochrane analysis observed no treatment effect of antibiotics over placebo but also included several other trials of low quality with high risk of bias and sparse data, which—according to the authors—made the results unreliable with inconsistent differences and high confidence intervals ( 17 ). This emphasizes the importance to select only high-quality trials with strict inclusion and exclusion criteria and similar or at least comparable follow-up periods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, strict study inclusion criteria with limitation to high-quality RCTs with reported follow-up intervals and the current definition of SBP resulted in a patient collective with low heterogeneity of IRRs and allowed comparison over time with regard to IRRs of SBP and extraperitoneal infections. A recent Cochrane analysis observed no treatment effect of antibiotics over placebo but also included several other trials of low quality with high risk of bias and sparse data, which—according to the authors—made the results unreliable with inconsistent differences and high confidence intervals ( 17 ). This emphasizes the importance to select only high-quality trials with strict inclusion and exclusion criteria and similar or at least comparable follow-up periods.…”
Section: Discussionmentioning
confidence: 99%
“…A recent Cochrane analysis including 23 studies could not find a significant benefit of antibiotic prophylaxis to prevent death or serious complications. However, many studies were of low quality, resulting in sparse data and high risk of bias ( 17 ). Thus, the type of antibiotic prophylaxis remains controversial ( 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…Again, results suggest that only low-quality evidence supports the superiority of rifaximin over norfloxacin or other systemic antibiotics for either primary or secondary SBP prophylaxis (6,62,63) .…”
Section: Effects Of Rifaximin On Bacterial Infectionsmentioning
confidence: 94%
“…42 However, because of its activity against bacterial translocation and its good safety profile, the use of rifaximin as a disease-modifying agent represents an attractive option. In addition, several observational studies and a few small-scale RCTs [47][48][49][50][51][52][53][54][55][56][57][58][59] have associated rifaximin treatment with a better control of difficult-to-treat/refractory ascites, 47,48 the reduced incidence of decompensation, all-cause hospitalisations and readmissions, SBP, variceal bleeding, and acute kidney injuryhepatorenal syndrome (AKI-HRS) with a decreased risk of renal replacement therapy. [49][50][51][52][53][54][55][56] An improvement in mortality has also been suggested in some studies.…”
Section: Key Pointmentioning
confidence: 99%
“…[49][50][51][52][53][54][55][56] An improvement in mortality has also been suggested in some studies. 48,52 However, the overall low quality of the evidence available, as highlighted by several meta-analyses, [57][58][59] precludes the possibility of reaching any definite conclusion on the global impact of rifaximin on the course of decompensated cirrhosis.…”
Section: Key Pointmentioning
confidence: 99%